Selection of physiologic quality and yielding in the S2 lines derived from four tropical populations of maize (Zea mays L.) - Navarro, Enrique; Vega, Cristina; Narváez, Fernando; Córdova, Hugo (Agronomía Mesoamericana, 2016)
This study was carried out in 1993 to evaluate S2 lines from four maize tropical populations improved by reciprocal recurrent selection. These lines were evaluated under field and laboratory conditions, the latter one to determine physiology quality. The main goal was to measure genetic variability within and among populations for traits such as grain yield, vigor and germination and to select the best lines under field and laboratory conditions. The combined analysis of variance showed great genetic variability among the S2 lines within and among populations for grain yield, days to flower, plant and ear height, among others. The maximum genetic variability was observed on the lines from population 43 and pool 23 for most of the traits, although the latter showed a greater genetic variability for grain yield. Besides, it is important to mention that the above populations included the best genotypes for grain yield, germination and vigor. Taking into account the above mentionel agronomic traits, fifteen lines were selected; 2 belong to population 43* pool 20, 2 from pool 19* pool 23, 8 from population 43, and 3 from pool 23. These results confirm the genetic superiority of the lines from populations 43 and pool 23, so that these populations should be recommended for future genetic improvement by reciprocal recurrent procedures.